Efficacy of air polishing for the non‐surgical treatment of peri‐implant diseases: a systematic review. (16th October 2015) - Schwarz, Frank; Becker, Kathrin; Renvert, Stefan
Abstract: Focused Question: In patients suffering from peri‐implant diseases, what is the efficacy of air polishing on changing signs of inflammation compared with control treatments (i.e. alternative measures for plaque removal with or without adjunctive antiseptic and/ or antibiotic therapy)? Material & Methods: After electronic database and hand search, 10 full‐text articles were independently screened by two reviewers. Finally, a total of five studies (six publications) fulfilled the inclusion criteria. The weighted mean difference (WMD) [ p ; 95% CI] in bleeding on probing‐ (BOP) (primary outcome) and probing pocket depth‐ (PD) reductions was estimated using a random effect model. Results: All studies reported on residual BOP scores after therapy. A narrative data synthesis did not reveal any major improvement of bleeding index/ BOP or disease resolution following air polishing over mechanical debridement at mucositis sites. At peri‐implantitis sites, WMD in BOP reduction between test and control (mechanical debridement with or without local antiseptic therapy, Er:YAG laser) groups was −23.83% [ p  = 0.048; 95% CI (−47.47, −0.20)] favouring air polishing over control measures. Conclusions: While glycine powder air polishing is as effective as the control treatments at mucositis sites, it may improve the efficacy of non‐surgical treatment of peri‐implantitis over the control measures investigated. A complete disease resolution was commonly not obtained.